Health care: automatic handwash / Muhammad Azam Zulkefeli, Wan Muhamad Auf Wan Mohd Raziff and Mohamad Iman Jamaluddin - Zulkefeli, Muhammad Azam; Wan Mohd Raziff, Wan Muhamad Auf; Jamaluddin, Mohamad Iman (2014)
This project is to build and test a system of automatic hand wash. This system is more advanced than conventional hand washing and it is designed to improve the life of a system that is much easier to wash your hands. For example, water, soap and hair all integrated into the system. The machine controls the water, soap and dryer automatically in sequence using the PIC16F877A microcontroller. Water, soap and hand dryers are controlled by programming code programmed into PIC16F877A microcontroller. Therefore, this project uses three infrared sensors to detect user's hand and give signal to the water, soap and dryer for operation respectively. If the infrared sensor (sensor arm) detects the user's hand, the water will be flowing to wash their hands. After that, the infrared sensor (sensor arm) detects the user's hand and the soap will be flowing that serves as a dirt remover in the hands of consumers. Then the infrared sensor (sensor arm) will detect the user's hand, the water will flow out again to remove the effects of soap on hand users. Lastly, the dryer will activate depending on the user's hand.